PENGARUH IMPLEMENTASI PROGRAM PRO-SELF TERHADAP KECEMASAN DAN DEPRESI PASIEN KEMOTERAPI DI RUANG PENYAKIT DALAM IRNA 1 RSUP DR. SARDJITO YOGYAKARTA - , JIHANNI MUSTIKA M ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Chemotherapy cause physiological and psychological side effects. Psychological symptoms that can occur such as anxiety and depression. Psychosocial problems can be overcome with improved patient coping through the provision of information , improved system suppor. PRO-SELF program was designed to increase self-care skills for adult patients undergoing cancer therapy include the information, skills and support cancer patients can engage effectively and consistently independent in managing severity of symptoms associated with the disease or treatment the disease can be minimized . Objective: To identify the effect of implementation PRO-SELF Program to anxiety and depression in chemotherapy patients . Methods : This study used a pre- experimental, one-group pre-test â post-test design involving 40 respondents to the inclusion criteria in this study all chemotherapy patients, aged less than 65 years , screening patients with ECOG 0-2 scale , respondents are willing to be . Exclusion criteria that cancer patients who have a history of psychiatric disorder. Respondents were provided with information , skills to reduction chemotherapy side effects and provide support with telephon when patient at home. Measurement of anxiety and depression using Hospital Anxiety Depression Scale (HADS) questionnaires and analyzed using the Wilcoxon test with 95% level of significancy. Results: Decrease respondents anxiety from pre-test to post-test with significancy 0001, so it is there a significant difference. Depression respondents changed from pre-test to post-test with significancy 0.258 , so that non-significant difference. Conclusions: Implementation of the PRO-SELF Program can effectively reduce patient anxiety chemotherapy. Yet it can not be effective in reducing depression.